Human Capital Investments and Labor Mobility - Eriksson, Göran (Journal of Labor Economics, 1991)
This article integrates human capital theory with a theory of information accumulation and labor mobility. A model is constructed for the determination of human capital accumulation, job matching, and mobility that accounts for heterogeneity on both sides of the labor market. The model provides explanations for observable relationships between earnings, mobility, age, and job tenure. It also provides comparative static results of how the labor market equilibrium is affected by changes in the economic environment.